Pengaruh Video Animasi Pembelajaran dan Buku Ajar Cetak terhadap Hasil Belajar Praktik Ibadah - Achmadi; Bulkani Ardiansyah (CENDEKIAWAN, 2023)
The purpose of this study was to determine the effect of animated learning videos and printed textbooks on learning outcomes of religious practices. The population of this study was only students of SD Muhammadiya Pahandudut Palangkaraya and the sample was third grade students of SD Muhammadiya Pahandudut Palangkaraya. Appropriate equipment and data collection is required depending on the phenomenon the researcher wants to study. Student observation and learning achievement tests were used as data collection techniques in this study. The key findings from this study are the applications used by researchers to help improve student learning outcomes. The results of this study indicate that: (1) Learning video animation has a major effect on the learning outcomes of the practice of faldu prayer. (2) The learning outcomes of the fardhu prayer groups of students using learning animation videos were higher than the fardhu prayer group of students using printed textbook media.